The adoption by persons with disabilities - Alma María Rodríguez Guitián (Oñati Socio-Legal Series)
According to Article 23 of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) States Parties shall ensure the rights and responsibilities of such persons with regard to adoption of children. This article has a limited application in practice due to a traditional prejudice towards sexuality and motherhood/parenthood of these people, even proposing the adoption of their biological children. This contribution focuses on the analysis of the configuration of adoption in the aforementioned Article 23.2 CRPD, based on significant examples of Comparative Law. First, it studies the health and financial requirements for adopters, which often hide direct or indirect discrimination against the people with disabilities. Second, this paper explores the meaning of the concept of `supportˊ, which is aimed at ensuring that persons with disabilities can adopt on an equal basis with others. Third, it analyzes the scope of the expression ˊin all cases the best interests of the child shall be paramountˊ, with a view to examining whether it jeopardises the effectiveness of Article 23.2 CRPD in practice.